Interpreting nature : the emerging field of environmental hermeneutics - Clingerman, Forrest (Groundworks : ecological issues in philosophy and theology, 2014)
The 20th century saw the rise of hermeneutics, the philosophical interpretation of texts, and eventually the application of its insights to metaphorical 'texts' such as individual and group identities. It also saw the rise of modern environmentalism which evolved through various stages in which it came to realize that many of its key concerns - 'wilderness' and 'nature' among them - are contested territory that are viewed differently by different people. This title brings together leading voices at the intersection of these two increasingly important philosophical discussions.